PENGARUH SAAT APLIKASI PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS KEDELAI (Glycine max.L.Merril) - Agus Santi; Aslim Rasyad; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research was to determine suitable nitrogen application time on several soybean varieties. This research was conducted in the agricultural experimental unit, Agriculture Faculty, Riau University. The study was arranged in randomized block design in which three soybean varieties ie, Grobogan, Argomulyo and Kaba were grown and fertilized with four application methods. The methods of application were no N fertilizer as control, 25 kg N applied atplanting date, 25 kg N applied at 35 days after planting, and 25 kg N applied atplanting  followed 25 kg N at 35 days after planting. Every tretment combination was repeated three times. Traits measured were plant height, number of main branches, plant biomass at 28 and 35 days after planting, crop groth rate, leaf area index, flowering date, harvesting date, number of filled pods, seed weight per plant, grain yield per m2, and harvest index. The data were then analysed by analyses of variance followed by least  significant difference at 5%.  There were differences among varieties on all characters observed except for plant biomass at 28 days after planting and harvest index. Application of N fertilizer with a rate of 25 kg per ha at planting and followed by the same rate at 35 days after planting in all varieties resulted faster flowering date, earlier harvest date, more filled pods, greater seed weight per plant and higher grain yield compare to other application time.Keywords : time of nitrogen fertilizer, plant growth rate, yield components